2017
DOI: 10.1021/acsami.7b00912
|View full text |Cite
|
Sign up to set email alerts
|

Printable Transfer-Free and Wafer-Size MoS2/Graphene van der Waals Heterostructures for High-Performance Photodetection

Abstract: Two-dimensional (2D) MoS/graphene van der Waals heterostructures integrate the superior light-solid interaction in MoS and charge mobility in graphene for high-performance optoelectronic devices. Key to the device performance lies in a clean MoS/graphene interface to facilitate efficient transfer of photogenerated charges. Here, we report a printable and transfer-free process for fabrication of wafer-size MoS/graphene van der Waals heterostructures obtained using a metal-free-grown graphene, followed by low-te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
76
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 90 publications
(80 citation statements)
references
References 33 publications
(60 reference statements)
4
76
0
Order By: Relevance
“…Figure (c) shows the photocurrent sharply increased to the saturation within 84 ms (0–80%) and decreased within 30 ms (100–20%). The response time is not fast but comparable to other reported works using the similar heterostructure . The main limiting factor could arise from the cleanliness of the transferred film and the part of the film attaching to the sidewall of the waveguide.…”
supporting
confidence: 77%
See 1 more Smart Citation
“…Figure (c) shows the photocurrent sharply increased to the saturation within 84 ms (0–80%) and decreased within 30 ms (100–20%). The response time is not fast but comparable to other reported works using the similar heterostructure . The main limiting factor could arise from the cleanliness of the transferred film and the part of the film attaching to the sidewall of the waveguide.…”
supporting
confidence: 77%
“… (26 mA W −1 ), and ref. (12.3 mA W −1 ), which shows the enhanced light–matter interaction of waveguide‐integrated 2D material photodetectors. The responsivity of our device is limited mostly by the inevitable degradation of the material performance during the wet‐transfer method, which can be further improved using a transfer‐free grown MoS 2 /graphene heterostructure .…”
mentioning
confidence: 92%
“…Apart from the high sensitivity to various wavelengths, the present BPQDs@PdSe 2 /Si heterojunction photodiode exhibits a relatively fast response speed, which is comparable with that of other TMDs based detectors . During the temporal response study, the pulsed optical signal was generated by 780 nm laser diode controlled by a function generator, and the transient photoresponse was recorded by an oscilloscope .…”
Section: Resultsmentioning
confidence: 72%
“…It should be pointed out that an opposite trend is expected since MoS 2 with smaller layer numbers would be more affected by graphene. For a single‐layer of MoS 2 grown (using CVD) on graphene, the peaks for the E 1 g and A 1 g modes are shifted to ≈386 and ≈406 cm −1 , respectively, thus the spacing between the peaks is ≈20 cm −1 . It has been shown that the peaks' positions and thus the spacing between them is changed as a function of the layer number, suggesting the Raman peak shifts for TMDs are primarily from the increased number of layers in the TMD nanodomes/graphene vdW heterostructures.…”
Section: Resultsmentioning
confidence: 99%
“…The small precursor thickness typically in the range of a few nm and clean graphene surface are the key to TMD nanodome formation. On graphene directly grown on Si/SiO 2 substrates, it was found that the TMD forms a continuous layer due to the growth defect–induced rough surface of graphene . In addition, when the dipping times were increased to four times, the morphology of the MoS 2 evolves from nanodomes, mixture, and continuous layers.…”
Section: Methodsmentioning
confidence: 99%